Kebijakan Pemerintahan Joko Widodo dalam Menghadapi Ancaman Cyber di Sektor Infrastruktur Energi Indonesia - Baptista Pradevi; Indra Wisnu Wibisono; Roberto OC Seba (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Energy infrastructure is a strategic sector for Indonesia's economic stability and national resilience. However, digitalization increases the risk of cyberattacks such as malware and the hacking of industrial control systems. This study analyzes the effectiveness of cybersecurity policies during the Joko Widodo administration using a qualitative approach through a literature review of regulations, institutional reports, and academic studies. The results show that the government has established a fairly robust regulatory and institutional framework, including Presidential Regulation No. 53 of 2017, Presidential Regulation No. 82 of 2022, and Law No. 27 of 2022. Furthermore, efforts to strengthen cybersecurity have been made through collaboration between PLN and BSSN, the establishment of CSIRT (Computer Security Incident Response Team), and improvements in human resource quality through training and certification. However, policy implementation still faces challenges such as limited expertise, gaps in security standards, and digital vulnerabilities due to partially integrated systems. Therefore, human resource capacity building, regular security audits, and more adaptive policies in response to global technological developments and increasingly complex threats are needed.